PENGARUH DISIPLIN KERJA DAN PENDELEGASIAN WEWENANG TERHADAP PRESTASI KERJA KARYAWAN PADA PT. AKADEMI MANDIRI MEDAN - YUNIRIDA GULO; H. D. MELVA SITANGGANG; HAYUNIMAH SIREGAR (JURNAL ILMIAH KOHESI, 2022)
PT. Akademi Mandiri Medan is one of the companies engaged in the field of contractors. Therefore, a good leader muststrive so that his subordinates have good discipline and must provide motivation in carrying out good discipline in anorganization. Regulations are necessary to create a good order in the company. With good order, morale, work morale,efficiency and effect of employee work will increase. The purpose of this study is to find out the influence of Work Disciplineand Simultaneous Delegation of Authority on Employee Work Performance on PT. Mandiri Medan Academy either partiallyor simultaneously. The population in this study was 57 people and the respondents sampled in this study were 57respondents using saturated samples. The results showed that Work Discipline (X1) had no effect on EmployeePerformance (Y). While delegation of authority (X2) has a significant effect on employee performance. Together, thevariables of Work Discipline and Delegation of Authority have a significant effect on employee performance.